APPLICATION FOR DONATION Â€“ UP LIFE - Carvalho, Caàque Oliveira; Ribeiro, Carlos Eduardo C.; Cardoso, Lorrayne Annyelly P.; Barreira, Luiz Henrique Bispo; Santos, Guilherme de Moura; Santos, Gustavo Gomes dos; Santos Júnior, William Pereira dos; Marins , Walquària Fernandes (CIPEEX, 2022)
WITH THE OCCURRENCE OF THE COVID-19 PANDEMIC, WHICH TOOK THE LIVES OF SEVERAL PEOPLE AND BROUGHT TO THE SURFACE SOCIAL, SANITARY, ECONOMIC AND ENVIRONMENTAL IMPACTS, NUMEROUS PROBLEMS FOR THE POPULATION WERE TRIGGERED. AMONGST THEM, A RESEARCH CONDUCTED BY THE BRAZILIAN MINISTRY OF HEALTH NOTED AN ALARMING DROP IN BLOOD DONATION RATES AND A LACK OF STOCK IN BLOOD DONATION FACILITIES. IN ADDITION, A PUBLICATION BY THE UNIVERSITY OF SÃO PAULO (USP) STATES THAT STORING LEFTOVER MEDICATION IS A VERY COMMON HABIT AMONG BRAZILIANS AND, OVER TIME, WAS OBSERVED A LARGE INCREASE IN EXPIRING DRUGS AND MEDICINE. THE PROJECT AIMS TO RESEARCH, PLAN AND DEVELOP AN APPLICATION TO IMPROVE THE PROCESSES OF BLOOD AND DRUGS FOR LEUKEMIA TREATMENT DONATION. AIMING TO ENCOURAGE, INFORM AND RETAIN DONATION FREQUENCIES TO REACH HIGHER NUMBERS IN CONTRIBUTION RATES. VIA EXPLORATORY RESEARCHES, OBSERVATION, AND STUDIES DIRECTED TO THE THEMATIC AND WITH INTENTION OF FURTHER USE OF DATA COLLECTION AND HANDLING PRACTICES, WE SEEK A BETTER UNDERSTANDING OF THE PHENOMENA INVOLVING SUCH PROCESSES, GAINING KNOW-HOW ON THE REASONS FOR NON-DONORS AND INACTIVE DONORS. THUS, IMPLEMENTING POSSIBLE SOLUTIONS FOR CONTRIBUTION GATHERING WITHIN THE APPLICATION. SO FAR, THE RESULTS ACHIEVED OBTAINED ELEVEN ARTIFACTS OF THE REAL PROJECT, PRODUCED FROM CONCLUSIONS DRAWN WITHIN THE RESEARCH, ACHIEVING ESTABLISHED MILESTONES OF THE PROJECT.